The Incorporation of Thermocouples in Knitted Structures - Chughtai, Muhammad Tajammal (Engineering, Technology & Applied Science Research, 2023)
Recent developments in textiles have led to the manufacturing of a variety of fabrics. These developments include spacer fabrics, embroidered fabrics, embedded sensors in fabrics, ECG vests, etc. Electronic components are also being knit within fabrics. The study used a configuration of thermocouples, based on the Seebeck effect, knitted into the main structure using a variety of yarn filaments. The knitted fabric was tested against temperature variation to examine how it affects the impedance of the knitted thermocouples. The testing procedure produced promising results, as it showed that certain combinations of knitting materials may result in positive and negative temperature coefficients of the fabric. The combination of the tested materials provides a guide to developing similar structures for thermoelectric sensor applications.